The Influence of Top Management Support, Professionalism, and Work Motivation on Employee Performance - Azizah, Queen; Suyono, Joko; sari, Yunita; Rarasingtyas, Listyorini; Elisabeth, Damarsari Ratnasahara (INNOVATION RESEARCH JOURNAL, 2025)
The aim of this research is to analyze the influence of top management support, professionalism and work motivation on employee performance of General and Personnel Department of RSUD dr. Mohamad Soewandie Surabaya. The sample in this study were all employees of General and Personnel Department of RSUD dr. Mohamad Soewandie Surabaya numbered 43 people. The data collection technique uses a questionnaire, while the data analysis technique uses multiple linear regression. The research results prove that top management support, professionalism and work motivation have a partial and simultaneous effect on employee performance of General and Personnel Department of RSUD dr. Mohamad Soewandie Surabaya. Among these three variables, work motivation is proven to have a dominant influence on employee performance of General and Personnel Department of RSUD dr. Mohamad Soewandie Surabaya. Thus, the hypothesis which states that professionalism has a dominant influence on employee performance of General and Personnel Department of RSUD dr. Mohamad Soewandie Surabaya is not proven and rejected.